Implementación, experimentación y evaluación térmica de un calentador solar de agua en espiral, para la vivienda sustentable de la Facultad de la Energía, las Industrias y los Recursos Naturales no Renovables - Sáenz Sócola, Daniel Alejandro (2022)
The present titling work is a study carried out on an experimental type of solar heater with a spiral-shaped collector, which is of low power level and whose purpose is to obtain sanitary hot water in the sustainable office-type housing of the Faculty. Energy, Industries and Non-Renewable Natural Resources of the National University of Loja, taking advantage of the solar radiation that exists in the sector. The flat spiral collector prototype is based on the study of a conical spiral prototype, making changes to improve the operation of the latter. Depending on the topographic, climatic and economic conditions, the heater was selected, designed, built, implemented and evaluated using the methodology of Sixto Guevara Vásquez in the " Teoría para el diseño de calentadores solares de agua". The heater resulted in an efficiency of 37% during the test days, implementing a box design to conserve the heat produced during sunny hours. The collector is composed of a total of 11.5 revolutions of 3/4" polyethylene hose, having a total length of 26.9 m, the box has an area of (1.2 x 1.2) m2, height 10 cm, insulated with EPS aluminum foil and aluminum plates, the tank is designed for a capacity of 15.2 liters with float filling, and insulated with glass wool. Keywords: Collector, Experimentation, Solar Radiation, Sanitary Hot Water.